2019
DOI: 10.1111/jcmm.14375
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac‐specific overexpression of metallothionein attenuates L‐NAME‐induced myocardial contractile anomalies and apoptosis

Abstract: Hypertension contributes to the high cardiac morbidity and mortality. Although oxidative stress plays an essential role in hypertensive heart diseases, the mechanism remains elusive. Transgenic mice with cardiac overexpression of metallothionein, a heavy metal‐binding scavenger, were challenged with N G ‐nitro‐L‐arginine methyl ester (L‐NAME) for 14 days prior to measurement of myocardial contractile and intracellular Ca 2+ anomalies as well as cell signalling mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Some studies have revealed the role of oxidative stress in myocardial injury caused by cold stress through antioxidants. Metallothionein, a low molecular weight heavy metal-chelating antioxidant (Yang et al, 2019), significantly improves ROS overproduction, myocardial fibrosis, and myocardial contraction dysfunction caused by cold stress (Zhang et al, 2012a).…”
Section: Mechanism Of Myocardial Injury Induced By Cold Stress Oxidatmentioning
confidence: 99%
“…Some studies have revealed the role of oxidative stress in myocardial injury caused by cold stress through antioxidants. Metallothionein, a low molecular weight heavy metal-chelating antioxidant (Yang et al, 2019), significantly improves ROS overproduction, myocardial fibrosis, and myocardial contraction dysfunction caused by cold stress (Zhang et al, 2012a).…”
Section: Mechanism Of Myocardial Injury Induced By Cold Stress Oxidatmentioning
confidence: 99%
“…Likewise, the liver of offspring from zinc-deficient pregnant mice showed hypermethylation in the -820 CpG region of the MT2 gene but no methylation in the -480 to +140 region of this gene which contains metal responsive elements (MREs) [ 17 ]. MT has been shown to engage in heavy metal ions, such as zinc and copper transport, metabolism and homeostasis in tissue and cells [ 47 ]. MT methylation intensity was shown to be linked with the downregulation of gene expression [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that miR-490 also decreases in esophageal cancer, pancreatic cancer and other digestive cancers [ 29 ]. According to Li and other colleagues, miR-490-5p upregulation leads to inhibition on proliferation and induction on cell cycle arrest in G0/G1 phase in bladder cancer [ 30 ]. We illustrated that miR-490-5p exerted a similar effect in GC, which hindered malignant progression of the disease.…”
Section: Discussionmentioning
confidence: 99%